2014
DOI: 10.1097/aln.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Opening Injection Pressure Consistently Detects Needle–Nerve Contact during Ultrasound-guided Interscalene Brachial Plexus Block

Abstract: High OIP (≥15 psi) consistently detected NNC, suggesting that injection pressure monitoring may be useful in preventing injection against nerve roots during interscalene block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 25 publications
2
72
1
2
Order By: Relevance
“…Injection pressure monitoring (w [15) has been studied in cadaver models, comparing when the needle is intraneural [9] and when the needle lies close to the nerve root but does not puncture it [16]. These studies demonstrated that nerve block pressure injection monitoring is a useful tool in order to prevent an intrafascicular injection in noncompliant neural structures like the brachial plexus.…”
Section: Commentmentioning
confidence: 99%
“…Injection pressure monitoring (w [15) has been studied in cadaver models, comparing when the needle is intraneural [9] and when the needle lies close to the nerve root but does not puncture it [16]. These studies demonstrated that nerve block pressure injection monitoring is a useful tool in order to prevent an intrafascicular injection in noncompliant neural structures like the brachial plexus.…”
Section: Commentmentioning
confidence: 99%
“…One recent study has suggested that high opening injection pressures (100 kPa) detected using the BSmart may indicate needle-tonerve contact, and that avoiding injection when pressures are high may help to prevent intraneural injection and nerve injury [8].…”
Section: Nerve Block Injection Pressure Monitoringmentioning
confidence: 99%
“…In more than 80% they noted an intraneural needle insertion. Gadsden and his group measured minimal threshold currents during pre-contact and needle-nerve contact positions, as validated by ultrasound, at the interscalene plexus in 15 patients 15 . They noted a current intensity of 0.2-0.3 mA during the needle-nerve contact and currents between 0.5 and 0.7 mA in the pre-contact positions.…”
mentioning
confidence: 99%